Moments of suffering, pain and resilience: Somali refugees’ memories of home and journeys to exile - Pineteh, Ernest A. (Cogent social sciences, 2017)
This article is based on a collection of stories about victimisation and resilience, told by thirty Somali refugees in Cape Town, South Africa. It seeks to understand how this group of displaced persons remembers their experiences of homelessness in their ancestral home and their tumultuous journeys to exile. Using excerpts from the stories, the article attempts to unearth the multiple meanings of home and flight and connect these to the xenophobic experiences of Somalis residing in Cape Town. From the narratives, Cape Town-based Somali refugees attributed their resilience to xenophobic violence to their experiences of political and social violence in Somalia, their development of survival strategies and their ability to deal with hostilities during their journeys to exile.